Don`t throw the baby out with the bathwater: talent in swimming sprinting events might be hidden at early age - Brustio, P. R.; Cardinale, M.; Lupo, C.; Boccia, G. (International Journal of Sports Physiology and Performance, 2022)
Purpose : This study aimed to describe the career performance progression of elite early- and later-success international swimmers competing in sprint events (ie, 50 and 100 m).